What are they doing right? Tweeting right-wing intersectionality in Latin America. Issue 1 (2nd January 2023) - Ravecca, Paulo; Schenck, Marcela; Fonseca, Bruno; Forteza, Diego
ABSTRACT: Despite the contributions of intersectional approaches, the academic and political left is challenged by competing interests in class, gender, race, and other axes of inequality and power. The disconnect between research on political economy, on the one hand, and on culture and subjectivity, on the other, is stark in Latin American studies. In contrast, an emerging feature of the global radical right is the gathering of these dimensions in simultaneous attacks to different strands of progressive politics and scholarship. The enemy is defined in economic and cultural terms: thus, feminism is frequently referred to as an extension of communism while Marxism is understood as part of cultural conspiracies to destroy healthy families and normal lifestyles. We call this phenomenon right-wing intersectionality (RWI). Through a mixed-methods approach, the article explores how RWI manifests in 20 leading influencers, activists, and politicians. The research included the systematic content analysis of 30, 858 tweets.